Enhancement of the thermoelectric power factor by tuning the carrier concentration in Cu-rich and Ge-poor colusites Cu26+xNb2Ge6−xS32. Issue 19 (14th April 2020) - Bouyrie, Yohan; Chetty, Raju; Suekuni, Koichiro; Saitou, Noriyuki; Jood, Priyanka; Yoshizawa, Noriko; Takabatake, Toshiro; Ohta, Michihiro
Abstract : We demonstrate the high power factor (∼830 μW m −1 K −2 ) at 670 K for x = 0.5 in Cu26+ x Nb2 Ge6− x S32 . Abstract : Non-stoichiometric colusites Cu26+ x Nb2 Ge6− x S32 (0 ≤ x ≤ 0.7) were prepared by mixing elemental constituents in evacuated quartz tubes at 1323 K followed by hot-pressing at 973 K. Their thermoelectric properties were investigated over the temperature range of 300 K–670 K. X-ray diffractometry and transmission electron microscopy analyses revealed that all the samples have a well crystallized structure and consist of the ordered colusite phase in which Cu, Nb, and Ge cations occupy their respective atomic positions in the structure. Energy dispersive spectroscopy analysis showed the presence of sulfur-poor and cation-rich chemical compositions in all the samples. We demonstrate that the increase of x (Cu-rich and Ge-poor) leads to an increase of the carrier concentration, resulting in a high power factor of ∼830 μW m −1 K −2 at 670 K for the sample with x = 0.5. High-temperature sintering led to significant defects of sulfur and interstitial cations, which resulted in a low lattice thermal conductivity (∼0.4 W m −1 K −1 at 670 K). A ZT of 0.7–0.8 was achieved at 670 K irrespective of the value of x .